USING LOCAL CULTURE AS TEACHING MATERIALS FOR IMPROVING STUDENTS’ READING COMPREHENSION - Wulandari, Ayu Apriyesi; Vianty, Machdalena; Fiftinova, Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The objectives of this study were to find out whether or not there were significant improvements in descriptive reading comprehension achievement after the students were taught by using local culture materials and between the students who were taught by using local culture materials and those who were not. This study was a quasi-experimental research method that applied non-equivalent control group research design. The population of this study was the tenth-grade students of a private senior high school in Palembang in the academic year 2017-2018 and the number of sample was 70 students, who were selected by using a convenience sampling technique. A reading comprehension test was used to collect the data which were analyzed statistically by using paired and independent sample t-tests. The results of this study revealed that there was a significant improvement in descriptive reading comprehension achievement and the aspects of reading comprehension after the students were taught by using local culture materials. There was also a significant difference in descriptive reading comprehension achievement between the students who were taught by using local culture materials and those who were not. Therefore, it can be concluded that local culture can be used as teaching materials for helping students to improve their reading comprehension.Keywords: local culture materials, descriptive text, reading    comprehension, ten graders